Phase Separated Methylated Polybenzimidazole (O-PBI) Based Anion Exchange Membranes - Germer, Wiebke; Leppin, Janine; Kirchner, Carolina Nunes; Cho, Hyeongrae; Kim, Hyoung-Juhn; Henkensmeier, Dirk; Lee, Kwan-Young; Brela, Mateusz; Michalak, Artur; Dyck, Alexander (John Wiley & Sons Ltd., 2015)
Methylated polybenzimidazole (O-PBI) based anion exchange membranes with a degree of methylation of ca. 78% were prepared in the iodide, chloride, carbonate, bicarbonate, and hydroxide form. Swelling in water showed a high anisotropy for chloride and carbonate exchangedmembranes and a strong plasticizing effect of water was confirmed by DMA. Carbonate and bicarbonate exchanged membranes revealed an ionomer peak around 0.25 angstrom(-1) in SAXS measurements suggesting a phase separated morphology. Theoretical DFT calculations were used to characterize geometries and electronic structure of polymer models and interactions with different anions, and to rationalize the water uptake/swelling behavior.